PROSPECTS FOR THE DEVELOPMENT OF SMALL AND MEDIUM BUSINESS IN NAMANGAN REGION - Rahimova , Mohigul (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract. Objective. The purpose of the study is to analyze the five-year development of small and medium-sized businesses in Namangan region, and determine the future development prospects of the region. Methods. Methods such as synthesis, scientific knowledge, statistical analysis, factor analysis, comparison, comparison were used in the research process. Results. Based on the analysis carried out in the research, the growth points of the development of small and medium business in Namangan region are identified and the future directions of development are determined. Conclusion. We believe that the recommended information, analysis, and conclusion will serve the development of small and medium-sized businesses in the Namangan region in the future.